2020
DOI: 10.1002/wer.1304
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite‐shunt and biological phosphorus removal at low dissolved oxygen in a full‐scale high‐rate system at warm temperatures

Abstract: This study presents results from the City of St. Petersburg's (Florida) Southwest Water Reclamation Facility. This high‐rate BNR plant (SRT ~ 5 days; HRT < 8 hr) achieves combined bioP and shortcut simultaneous nitrification and denitrification (SND) via nitrite in a simple BNR configuration—an anaerobic–aerobic (A/O) process without mixed liquor recycle and a 25% unaerated fraction. N removal to low effluent and nitrate and nitrite ( NO3- +  NO2-) concentrations occurs mainly via SND by operating the aerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The intrinsic kinetics of these two groups of microorganisms including maximum growth rate and substrate half-saturations are crucial (Liu et al 2020). DO affects the diversity and kinetics significantly, thus DO control to manipulate the competition for oxygen between AOB and NOB is one of the main strategies in mainstream conditions (Pérez et al 2014;Jimenez et al 2020). The oxygen half-saturation constant for AOB is generally accepted to be lower than for NOB which creates a disadvantage for NOB to compete for oxygen at low concentrations (Sin et al 2008;Cao et al 2017).…”
Section: Nob Out-selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic kinetics of these two groups of microorganisms including maximum growth rate and substrate half-saturations are crucial (Liu et al 2020). DO affects the diversity and kinetics significantly, thus DO control to manipulate the competition for oxygen between AOB and NOB is one of the main strategies in mainstream conditions (Pérez et al 2014;Jimenez et al 2020). The oxygen half-saturation constant for AOB is generally accepted to be lower than for NOB which creates a disadvantage for NOB to compete for oxygen at low concentrations (Sin et al 2008;Cao et al 2017).…”
Section: Nob Out-selectionmentioning
confidence: 99%
“…The nitrite-shunt process has been successfully implemented in side-stream treatment (e.g. SHARON process (Mulder et al 2001)) and there is an interest to implement it in mainstream treatment in a single reactor (Jimenez et al 2020). However, it is not commonly applied due to the lack of complete understanding of the underlying mechanisms for NOB out-selection and carbon availability for denitritation under these conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of this research has been carried out at pilot and bench scale and has led to only two full-scale implementations: a trial of mainstream bioaugmentation of anammox granules from the sidestream with a retention screen on the mainstream WAS (Wett et al, 2015) and the reported discovery of PNA in a step-feed BNR process with low DO in a warm climate (Cao et al, 2018).There are examples of sustained full-scale NOB out-selection but it is typically in warmer climates, and it is not always clear how to repeat the success in other facilities (Cao et al, 2018;Jimenez et al, 2020). It seems clear that the stability, reliability, and overall effectiveness of NOB out-selection are limiting the implementation of full-scale mainstream PNA.…”
Section: Mainstream Pna/nitrite Shuntmentioning
confidence: 99%
“…In the drinking water treatment aspect, three mineral adsorbents were studied for alleviation of multiple contaminants in source water in Northeastern Brazil (Guimarães Neto & Aguiar, 2020), while effects of coagulant types and doses, as well as water properties, were evaluated for coagulation removal of different engineered nanoparticles in water (Ramirez Arenas, Ramseier Gentile, Zimmermann, & Stoll, 2020). In the municipal wastewater treatment field, simultaneous nitrite‐shunt and biological phosphorus removal were demonstrated at low dissolved oxygen in a full‐scale high‐rate water reclamation facility (St. Petersburg, Florida) (Jimenez et al., 2020); and the process optimization and kinetic behaviors of the struvite precipitation for phosphorus removal and recovery were studied (Wang, Tian, Wang, & Yan, 2020). Of these papers on treatment of industrial wastewater, two focused on dyes in textile wastewaters.…”
mentioning
confidence: 99%